2021
DOI: 10.1002/ecs2.3769
|View full text |Cite
|
Sign up to set email alerts
|

Sun bears use 14‐year‐old previously logged forest more than primary forest in Sabah, Malaysia

Abstract: Sun bears (Helarctos malayanus), arguably the least-known bear species, are endemic to Southeast Asia and are believed to be in rapid decline due to forest loss and poaching, which are severe threats across this region. It has been asserted that, unlike other forest-dependent, omnivorous bears, sun bears are especially sensitive to changes in forest composition and canopy closure because they often feed on fruits in the canopy. We investigated habitat use of sun bears in a region of Sabah, Malaysian Borneo, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 103 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…Even photos can be misidentified as to the species, since some bears look alike [65,66]. Some kinds of bear signs can be confused with that of other species, so to avoid misidentification it may be preferable to only rely on types of signs that are definitive (e.g., claw marks on trees; [67]). However, this can lead to a bias if the more reliably identified sign occurs in certain types of habitats (Figure 3).…”
Section: Presence Pointsmentioning
confidence: 99%
See 4 more Smart Citations
“…Even photos can be misidentified as to the species, since some bears look alike [65,66]. Some kinds of bear signs can be confused with that of other species, so to avoid misidentification it may be preferable to only rely on types of signs that are definitive (e.g., claw marks on trees; [67]). However, this can lead to a bias if the more reliably identified sign occurs in certain types of habitats (Figure 3).…”
Section: Presence Pointsmentioning
confidence: 99%
“…An alternate explanation for high rates of photo-capture under a dense canopy could be that bears tended to rest in shady areas to avoid heat stress [94]. Whereas other studies have confirmed that sun bears select for areas with high tree cover, a large number of studies have now demonstrated that sun bears are also widespread in degraded and successional forests in both the mainland and Borneo and Sumatra [67,[95][96][97][98][99]. Hwang et al also pointed to many other camera-trap studies that were not specifically directed at sun bears that have consistently shown high occupancy in forests 6-20 years after logging, and growing evidence that poaching is driving sun bear density more than habitat degradation [67,100].…”
Section: Sun Bearsmentioning
confidence: 99%
See 3 more Smart Citations